In Defence of the Human Being: Foundational Questions of an Embodied Anthropology - Fuchs, Thomas (Oxford University Press USA - OSO, 2021)
With the progress of artificial intelligence, the digitalization of the lifeworld, and the reduction of the mind to neuronal processes, the human being appears more and more as a product of data and algorithms. The book applies cutting-edge concepts of embodiment and enactivism to current scientific, technological and cultural developments.
Description based on publisher supplied metadata and other sources